ZAKAT LEMBAGA DALAM PERSPEKTIF EKONOMI ISLAM - Hermansyah Hermansyah (Program Studi Manajemen, 2017)
The formality of zakat leaves problems in determining who is subject to zakat. If we refer to the rules of classical fiqh, then the only assets that must be zoned for use are precious metals (gold and silver), livestock (camels, cows and goats), agriculture, commerce, mining and found goods. In fact, at present there are many large sources of income outside this sector. The world of industry, entertainment and other service businesses is a field of income that is far greater than that of farmers.